Cultural workers in-the-making. (August 2013) - Ashton, Daniel
This article explores the situated practices through which higher education students understand 'becoming' cultural workers. Drawing on research with a media production studio operated by a UK higher education institution, this article examines how students understand themselves as nascent industry professionals and workers 'in-the-making' and connects this with critical debates on cultural workforce issues. This article reveals that while the studio as a work-based learning environment can equip students with industry-relevant skills and perspectives, there can be a distance and disconnect with cultural workforce issues of insecurity and working conditions. In response, this article examines how higher education can offer potentially productive spaces and opportunities for reflecting on these issues.